Glutathione Peroxidase 3 Inhibits Prostate Tumorigenesis in TRAMP Mice. Issue 15 (21st June 2016) - Chang, Seo‐Na; Lee, Ji Min; Oh, Hanseul; Park, Jae‐Hak
Abstract : BACKGROUND: Glutathione peroxidase 3 (GPx3) is involved in protecting cells from oxidative damage, and down‐regulated levels of expression have been found in prostate cancer samples. We hypothesize that loss of the GPx3 increases the rate of prostate carcinogenesis and generated GPx3‐deficient transgenic adenocarcinoma of the mouse prostate (TRAMP) mice. METHODS: Prostate cancer incidence and progression were determined in TRAMP, TRAMP/GPx3 (+/−) HET, and TRAMP/GPx3 (−/−) KO mice at 8, 16, and 20 weeks of age. RESULTS: We found that GPx3 expression was decreased in TRAMP mice and not detected in GPx3 KO mice both in mRNA and protein levels. Disruption of GPx3 expression in TRAMP mice increased the GU tract weights and the histopathological scores in each lobes with increased proliferation rates. Moreover, inactivation of one (+/−) or both (−/−) alleles of GPx3 resulted in increase in prostate cancer incidence with activated Wnt/β‐catenin pathway. CONCLUSIONS: Our results provide the first in vivo molecular genetic evidence that GPx3 does indeed function as a tumor suppressor during prostate carcinogenesis. Prostate 76:1387–1398, 2016 . © 2016 Wiley Periodicals, Inc.